Perfecting Engineering and Technical Drawing:Reducing Errors and Misinterpretations - Hanifan, Ron (Springer, 2015)
This concise reference helps readers avoid the most commonplace errors in generating or interpreting engineering drawings. Applicable across multiple disciplines, Hanifan’s lucid treatment of such essential skills as understanding and conveying data in a drawing, exacting precision in dimension and tolerance notations, and selecting the most-appropriate drawing type for a particular engineering situation, “Perfecting Engineering and Technical Drawing” is an valuable resource for practicing engineers, engineering technologists, and students.